2019
DOI: 10.3390/app9132718
|View full text |Cite
|
Sign up to set email alerts
|

Usability Measures in Mobile-Based Augmented Reality Learning Applications: A Systematic Review

Abstract: The implementation of usability in mobile augmented reality (MAR) learning applications has been utilized in a myriad of standards, methodologies, and techniques. The usage and combination of techniques within research approaches are important in determining the quality of usability data collection. The purpose of this study is to identify, study, and analyze existing usability metrics, methods, techniques, and areas in MAR learning. This study adapts systematic literature review techniques by utilizing resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 120 publications
0
15
0
2
Order By: Relevance
“…Among scales/questionnaires, which constitute the technique most often reported, the most common usability assessment scales were the System Usability Scale [ 29 , 32 , 41 - 43 , 46 , 47 ] and the Post-Study System Usability Questionnaire [ 41 , 42 , 46 , 47 ]. The other scales/questionnaires include the Questionnaire for User Interaction Satisfaction [ 29 , 42 , 47 ], the Software Usability Measurement Inventory [ 32 , 42 ], the Usefulness, Satisfaction, and Ease of use Questionnaire [ 32 , 41 ], the Computer System Usability Questionnaire [ 32 , 47 ], the After-Scenario Questionnaire [ 46 , 47 ], the Perceived Useful and Ease of Use [ 32 ], the IsoMetrics usability inventory [ 32 ], the Health Information Technology Usability Evaluation Scale [ 32 ], the user Mobile Application Rating Scale [ 32 ]; the IBM ease of use [ 42 ], and the ISO 9241–11 Questionnaire [ 43 ]. In addition, several reviews have reported the use of nonvalidated questionnaires [ 32 , 41 , 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among scales/questionnaires, which constitute the technique most often reported, the most common usability assessment scales were the System Usability Scale [ 29 , 32 , 41 - 43 , 46 , 47 ] and the Post-Study System Usability Questionnaire [ 41 , 42 , 46 , 47 ]. The other scales/questionnaires include the Questionnaire for User Interaction Satisfaction [ 29 , 42 , 47 ], the Software Usability Measurement Inventory [ 32 , 42 ], the Usefulness, Satisfaction, and Ease of use Questionnaire [ 32 , 41 ], the Computer System Usability Questionnaire [ 32 , 47 ], the After-Scenario Questionnaire [ 46 , 47 ], the Perceived Useful and Ease of Use [ 32 ], the IsoMetrics usability inventory [ 32 ], the Health Information Technology Usability Evaluation Scale [ 32 ], the user Mobile Application Rating Scale [ 32 ]; the IBM ease of use [ 42 ], and the ISO 9241–11 Questionnaire [ 43 ]. In addition, several reviews have reported the use of nonvalidated questionnaires [ 32 , 41 , 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, parents reported a high level of satisfaction with the different AR applications [ 40 ]. In general, the literature evidences that caregivers and teachers reported that children with ASD improved social interactions through advancements in nonverbal communication, social engagement, and eye contact while using AR technology [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified the advantages provided by computerized learning of different functional and social skills [ 11 , 14 ]. Specifically, among the strengths of the use of technology in interventions addressed at children with ASD, the possibility to clearly define tasks, to keep the focus of attention, to minimize distractions, and to facilitate personal skills and strategies with a tool that can be used for many applications is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment employed three data collection methods: think-aloud protocol, observation, and interview [52]. The test conductor instructed participants at the beginning of the test to follow the think-aloud protocol so that participants could comment about their opinions, motivations, actions, and any other comments about the test experience.…”
Section: Prototype Evaluationmentioning
confidence: 99%